Empathy of Marine Aquaculture on Aquatic Products Consumption - Xilin, Le; Wu, Yingqi; Zeng, Yan; Ma, Ting; Wang, Yating; Zhang, Qingyu (Frontiers in Psychology, 2022)
The prolonged COVID-19 has caused a global lockdown and greatly impacts the supply chain and consumers’ consumption behavior of aquatic products. Specifically, consumers’ increasing awareness of environmental protection drives the marine aquaculture enterprises to supply green products and establish empathy with consumers in a bid to achieve sustainable consumption. This paper conducts a study on the international green marketing paths of marine aquatic products through PLS-SEM analysis of the 407 valid samples collected from the questionnaire survey. The findings indicate that empathy marketing has a significant positive effect on consumers’ purchase intention; subjective norm has a significant positive effect on consumers’ purchase intention. Additionally, perceived behavior control has a significant mediating effect between consumers’ subjective norm and purchase intention; the consumption environment has a significant positive moderating effect on individual consumption intention. The study suggests that sustainable development can be further propelled by means of coordinating the consumers’ awareness of ecological environment protection and their enhanced consumption intention.